2022
DOI: 10.1155/2022/8446611
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Positive Psychotherapy on Depression and Alexithymia in Women Applying for a Divorce

Abstract: Background. The new therapeutic approach of positive psychotherapy has successfully treated severe mental disorders such as depression and mood disorders. However, existing research has not sufficiently measured the usefulness of this treatment in reducing depression and alexithymia. Objectives. This study thus examined the effectiveness of positive psychotherapy in reducing these two conditions in a specific population: Iranian women applying for the divorce. Methods. A total of 40 participants aged 20-40 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…he family is considered the smallest and most vital unit of society that can positively or negatively affect its members. Previous research has shown that divorce is one of the detrimental effects on a family, potentially reducing individual and family well-being and increasing mental health risks for its members (Khalili et al, 2022). This multifaceted phenomenon can lead to the development and exacerbation of physical and psychological disorders among individuals, including neurological, cognitive, emotional, and behavioral diseases (Hald et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…he family is considered the smallest and most vital unit of society that can positively or negatively affect its members. Previous research has shown that divorce is one of the detrimental effects on a family, potentially reducing individual and family well-being and increasing mental health risks for its members (Khalili et al, 2022). This multifaceted phenomenon can lead to the development and exacerbation of physical and psychological disorders among individuals, including neurological, cognitive, emotional, and behavioral diseases (Hald et al, 2020).…”
Section: Introductionmentioning
confidence: 99%